Methods of evaluating postural deviations of the spine used in national studies: a systematic review. - Filho, José Nunes da Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The spine related diseases have been increasing sharply and causing serious problems for public health. Having a postural assessment with one of the important factors in the prevention and/or treatment of these problems. Objectives: To determine which methods of spinal postural assessment has been used in studies and national journals published recently. Methods: This study is a systematic review, which followed the recommendations (PRISMA) “Transparent report of Systematic Reviews and Meta-analysis.” The search data Began with the choice of key terms and synonyms following the Health Sciences Descriptors DeSC and MeSH (Medical Subject Headings). Due to achieve the main objective of the research, we selected only studies of national authors and journals published between the year 2013 to Feb/2014, yet fitting, made any kind of spinal postural assessment. Conducted a descriptive statistical checking the frequency percentages by software (IBM ® SPSS ® Statistic, vs 21, New York/USA 2012. Results: 25 studies were included, and the methods of evaluation were: photogrammetry (36.7%, n =11); Posturógrafo (16.7%, n=5); X-Ray (10%, n=3); Postural Visual Evalution (23.3%, n=7) Goniometry (3.3%, n=1). Conclusions: it is concluded between national studies photogrammetry is the postural assessment methods most used today.